Tata Kelola Kolaboratif dalam Pembangunan Ekonomi Lokal: Studi Kasus BUMDes Guwosari Maju Sejahtera - Samosir, Winata Masniari; Agani, M Wahyu; Puteri, Nuraisya Handyka; Ardiansyah, Firhan; Lorang, Fransiska Devy (Politika: Jurnal Ilmu Politik, 2025)
Village-Owned Enterprises (BUMDes) are pivotal in local government strategies to boost rural economic growth, enhancing the quality of life and economic well-being in rural communities. This research examines the collaborative governance practices of BUMDes Guwosari Maju Sejahtera, focusing on aspects such as vision, accountability, collaborative capability, leadership, management capability, and procedural formalization. The study also evaluates the contribution of BUMDes Guwosari Maju Sejahtera to local economic development, considering job creation, human resource skill development, business activities, and environmental quality. The findings indicate that BUMDes Guwosari Maju Sejahtera has successfully built strong synergies with village governments, communities, and businesses to enhance local welfare. However, areas for improvement include formalizing vision and mission in planning documents, enhancing financial management for better accountability, and improving internal knowledge management for sustainable innovation.